Một số giải pháp tự học giúp giảng viên đại học nâng cao năng lực ngoại ngữ - Nguyễn , Thúy Hạnh (Tạp chí Giáo dục, 2022)
Nowadays, using foreign languages is an urgent need for university lecturers, serving many different purposes in their profession as well as in life. However, there are many obstacles that prevent one from succeeding in learning a foreign language. The challenges of learning a foreign language are discussed in this article, including lacking the appropriate learning method, motivation, self-confidence, as well as limited language input. Self-study solutions are also provided to assist university lecturers in making their own study plans, as well as to offer training faculties and universities with implications for appropriate policies that would support and encourage their lecturers to learn foreign languages.